ANALISIS PENGEMBANGAN USAHA ALAS KAKI MELALUI PENDEKATAN BUSINESS MODEL CANVAS DI KECAMATAN PARONGPONG KABUPATEN BANDUNG BARAT - Rosid, Abdul; Mulyana, Yayan (Business Preneur: Jurnal Ilmu Administrasi Bisnis, 2023)
CV Dian Nur Purnama is a family-owned company as well as one of the leading SMEs in Parongpong District, West Bandung Regency, which is engaged in the trading and manufacturing industry of Sirmione branded footwear products. There are several problems faced by CV Dian Nur Purnama in developing its business as follows: the foresight in increasing strong determination of raw material quality is still using synthesis rather than leather and the quantity of production is still lacking due to constraints on limited raw materials then providing motivation and increasing HR creativity (limited availability of labor in certain skills when requiring more workers when there are large orders). The Business Model Canvas which changes a certain method in identifying a more detail type of business that is being or will be undertaken, consists of nine key elements that are integrated with one another, and includes strategic analysis internally and externally for a business unit. Nine key elements, namely: (1). Customer Segment, (2). Value Proposition, (3). Channels, (4) Customer Relations, (5). Income Stream, (6). Primary Resources, (7). Main Activity, (8). Partnership Relations, (9). Cost Structure. The research method used is descriptive qualitative. Data collection techniques through observation, interviews, and documentation. The analytical process of data analysis before being in the field, and data analysis in the field includes: data reduction, data presentation, and verification. The results obtained show that most of CV Dian Nur Purnama has strengths in customer segments, value proposition, channels, customer relationships, main resources, main activities, partnership relationships, and cost structure. A small number of competitors are a threat to the sustainability of CV Dian Purnama. Companies have weaknesses in obtaining sources of license revenue, advertising, or when problems occur within the organization. The company continues to maintain or further improve its strengths, minimizes weaknesses, the company must maximize the company's sources of income, as well as inevitable threat which is making competitors become partners. Keywords: Business development, Business Model Canvas